Issues in the Management of Esophagogastric Cancer in Geriatric Patients - Won, Elizabeth (Surgical oncology clinics of North America, 2017)
Esophagogastric cancers predominantly affect older adults; however, older patients are less likely to be recommended for both curative and palliative treatment. Older patients have unique challenges that need to be addressed during their oncologic care. Tools such as complete geriatric assessments may help to better identify fit older adults and stratify patients for aggressive treatment strategies. This review evaluates the current knowledge and the remaining challenges in optimally managing elderly patients with esophagogastric cancers.